Trehalose and a calcium chelator for ram semen cryopreservation - Bittencourt, Rodrigo Freitas; Ribeiro Filho, Antonio de Lisboa [UNESP]; Lima, Marcos Chalhoub Coelho; Bittencourt, Marta Vasconcelos; Biscarde, Carmo Emanoel Almeida; Bicudo, Sony Dimas [UNESP]; Oba, Eunice [UNESP] (Universidade Federal do Paraná, 2014)
Twenty semen samples from ten rams of the Santa Inês breed were cryopreserved with the goal of verifying the effect of trehalose addition (100mOsmol) (group 1 -TRIS+TRE) to a Tris-egg yolk-glycerol extender (group 2 -TRIS), associated or not to the calcium chelator EDTA (group 3 -TRIS+TRE+EDTA), on the post-thaw sperm viability. After evaluation, the diluted semen samples were cooled at 5C and frozen in liquid nitrogen steam. After thawing, the kinetic sperm parameters were analyzed by a computer analyses system (CASA). The sperm viability was observed by using the multiple sperm parameter staining with propidium iodide (PMI, plasmatic membrane integrity), JC-1 (MMP, mitochondrialmembrane potential) and FITC-PSA (ACI, acrosomal integrity). The statistical analysis was performed using the SAS software, applying the MEANS procedure for descriptive analysis and the GLM procedure with the Student-Newman-Keuls test (SNK) for comparisonof sperm parameters among different groups(with P<0.05). The percentage of total and progressive motility post-thaw were the greatest (P<0.05) for the TRIS group in relation to trehalose ones. The PMI, MMP, and ACI rates (%) did not present differences (P>0.05) among the groups. It can be concluded that the trehalose addition to the TRIS extender, associated or not to EDTA, had detrimental effect on cryosurvivalram sperm.

Vinte amostras de semen de dez carneiros da raça Santa Inês foram criopreservadas com oobjetivo de verificar o efeito da adição de trealose (100mOsmol) (grupo 1 –TRIS+TRE) ao diluidor Tris-gema de ovo-glicerol (grupo 2 –TRIS), associado ou não ao quelante de cálcio EDTA (grupo 3 –TRIS+TRE+EDTA), sobre a viabilidade espermática pós-descongelação. Após avaliação, as amostras diluídas foram resfriadas à 5oC e congeladas em vapor de nitrogênio líquido. Após descongelação, os parâmetros de cinética espermática foram analizados por um sistema computadorizado (CASA). A viabilidade espermática foi observada através da coloração para avaliação multi-paramétrica com iodeto de propídio (MPI, membrana plasmática íntegra), JC-1 (PMM, potencial de membrana mitocondrial) e FITC-PSA (IAC, integridade acrossomal). A análise estatística foi realizada através do programa estatístico SAS, aplicando o procedimento MEANS para a análise descritiva e o procedimento GLM com o teste de Student-Newman-Keuls (SNK) para a comparação dos parâmentros espermáticos entre os diferentes grupos (com P<0,05). O percentual de motilidade total e progressiva pós-descongelaçào foram maiores (P<0,05) para o grupo TRIS em relação aos grupos com trealose. A taxas (%) de MPI, PMM e IAC não apresentaram diferenças (P>0,05) entre os grupos. Pode-se concluir que a adição da trealose, associada ou não ao EDTA, proporcionou efeito negativo para criopreservação do sêmen ovino.
Trealose e um quelante de cálcio para a criopreservação do semen ovino
Keywords: Ovis aries; Frozen semen; Hyperosmotic extender; Ovis aries; Sêmen congelado; Diluidor hiperosmótico